The utilisation of palm oil and its solid waste products as fuel; Decentralized and hierarchical control of robot manipulators; Thermal characteristics of Malaysian building envelopes; Travelling wave solutions for some nonlinear evolution equations; Relationships between engineering properties and microstructural characteristics of mortar containing agricultural ash; Magnetic resonance imaging of solids using oscillating field gradients [mikrofilem] - Farid Nasir Ani, 1957-; Johari Halim Shah Osman; Mohd. Nor Mohamad; Salihuddin Radin Sumadi; Yaacob Mat Daud; Kannan, K. S. (Sekudai : UTM., 1991)
Thesis (Ph D)